2010
DOI: 10.1117/12.856382
|View full text |Cite
|
Sign up to set email alerts
|

The SALT HRS spectrograph: final design, instrument capabilities, and operational modes

Abstract: The high-resolution échelle spectrograph, SALT HRS, is at an advanced stage of construction and will shortly become available to the user community of the Southern African Large Telescope (SALT). This paper presents a commentary on the construction progress to date and gives the instrument's final specification with refined estimates for its performance based on the initial testing of the optics and the science-grade detectors. It also contributes a discussion of how the fibre input optics have been tailored t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 5 publications
0
31
0
Order By: Relevance
“…Since HD 42659 is the only roAp star known to be in a spectroscopic binary system (Hartmann & Hatzes 2015), it provides us with the opportunity to test whether the binary companion affects the pulsations in the Ap star. To that end, we obtained 27 spectra with the High Resolution Spectrograph (HRS; Bramall et al 2010;Crause et al 2014) mounted on the Southern African Large Telescope (SALT; Buckley et al 2006). Observations were taken in High Resolution (HR) mode, R ≃ 65 000, with an integration time of 158 s. The signal-to-noise ratio varied between about 100 and 150 in the central region of the spectrum, dependent on observing conditions.…”
Section: Spectroscopymentioning
confidence: 99%
“…Since HD 42659 is the only roAp star known to be in a spectroscopic binary system (Hartmann & Hatzes 2015), it provides us with the opportunity to test whether the binary companion affects the pulsations in the Ap star. To that end, we obtained 27 spectra with the High Resolution Spectrograph (HRS; Bramall et al 2010;Crause et al 2014) mounted on the Southern African Large Telescope (SALT; Buckley et al 2006). Observations were taken in High Resolution (HR) mode, R ≃ 65 000, with an integration time of 158 s. The signal-to-noise ratio varied between about 100 and 150 in the central region of the spectrum, dependent on observing conditions.…”
Section: Spectroscopymentioning
confidence: 99%
“…A spectroscopic survey of stars classified as helium-rich subdwarfs, especially He-sdB or sdOD using 8m class telescopes has been undertaken. This paper reports an observation of one such star obtained with the high-resolution spectrograph (HRS) on the Southern Africa Large Telescope (SALT) (Buckley et al 2006;Bramall et al 2010;Crause et al 2014) 2 OBSERVATIONS GALEX J184559.8−413827 (α2000 = 18…”
Section: Introductionmentioning
confidence: 99%
“…New observations were obtained with the High Resolution Spectrograph (HRS: R ≈ 43 000, λλ = 4100 − 5200Å Bramall et al 2010) of SALT during 2015 and 2016 on the dates shown in Table 1. The spectra were reduced to order-by-order wavelength calibrated rectified form using the SALT pipeline pyHRS (Crawford et al 2016); orders were stitched into a single spectrum using our own software.…”
Section: Instrumentmentioning
confidence: 99%